EEG for good outcome prediction after cardiac arrest: A multicentre cohort study - Turella, S; Dankiewicz, J; Ben-Hamouda, N; Nilsen, K B; Düring, J; Endisch, C; Engstrøm, M; Flügel, D; Gaspard, N; Grejs, A M; Haenggi, M; Haffey, S; et al. (Resuscitation, 2024)
AIM: Assess the prognostic ability of a non-highly malignant and reactive EEG to predict good outcome after cardiac arrest (CA). METHODS: Prospective observational multicentre substudy of the "Targeted Hypothermia versus Targeted Normothermia after Out-of-hospital Cardiac Arrest Trial", also known as the TTM2-trial. Presence or absence of highly malignant EEG patterns and EEG reactivity to external stimuli were prospectively assessed and reported by the trial sites. Highly malignant patterns were defined as burst-suppression or suppression with or without superimposed periodic discharges. Multimodal prognostication was performed 96 h after CA. Good outcome at 6 months was defined as a modified Rankin Scale score of 0-3. RESULTS: 873 comatose patients at 59 sites had an EEG assessment during the hospital stay. Of these, 283 (32%) had good outcome. EEG was recorded at a median of 69 h (IQR 47-91) after CA. Absence of highly malignant EEG patterns was seen in 543 patients of whom 255 (29% of the cohort) had preserved EEG reactivity. A non-highly malignant and reactive EEG had 56% (CI 50-61) sensitivity and 83% (CI 80-86) specificity to predict good outcome. Presence of EEG reactivity contributed (p < 0.001) to the specificity of EEG to predict good outcome compared to only assessing background pattern without taking reactivity into account. CONCLUSION: Nearly one-third of comatose patients resuscitated after CA had a non-highly malignant and reactive EEG that was associated with a good long-term outcome. Reactivity testing should be routinely performed since preserved EEG reactivity contributed to prognostic performance.
Keywords: lidé středního věku; prospektivní studie; Predictive Value of Tests; kardiopulmonální resuscitace; prediktivní hodnota testů; Prognosis; Hypothermia, Induced; Male; EEG; Electroencephalography; lidé; senioři; prognóza; Prospective Studies; Aged; Cardiopulmonary Resuscitation; elektroencefalografie; zástava srdce mimo nemocnici; Out-of-Hospital Cardiac Arrest; Coma; ženské pohlaví; kóma; mužské pohlaví; terapeutická hypotermie; Outcome; Middle Aged; Humans; Reactivity; Cardiac arrest; Female